Some evidence of aviation fingerprint in diurnal cycle of cirrus over the North Atlantic - Graf, Kaspar; Mannstein, Hermann; Mayer, Bernhard; Schumann, Ulrich (DLR, 2010)
The diurnal cycle of aviation in the North Atlantic Region (NAR; 45° W – 10° W, 45° N – 55° N) shows a unique fingerprint dominated by two maxima due to rush-hours in west-bound resp. eastbound air traffic. We investigate the hypothesis that this signature can be found also in the diurnal cycle of cirrus coverage. Air traffic data were kindly provided by EUROCONTROL with adequate temporal and spatial resolution for this investigation. The cirrus cover is derived from Meteosat-8/9 SEVIRI data with a spatial resolution of about 5 km and a temporal resolution of 15 min using the cirrus detection algorithm MeCiDA (Krebs et al., 2007). Aviation induced cloud cover changes are derived from diurnal cycle of cirrus cover observed in NAR. We developed several response functions representing the effect of air traffic on cirrus coverage and applied fitting methods for determination of the fit parameters representing the statistical lifetime and the amount of AIC in NAR. Application of the fitting procedures to the air traffic density (ATD) allows us to reproduce the signature of cirrus coverage observed in cirrus coverage. The results are robust for investigations of sub regions of NAR with different signatures of initial ATD and shifts in the occurrence of maxima. Several satellite scenes illustrate the statistical behaviour in single scenes.